PEMBANGUNAN DAERAH DALAM PENGEMBANGAN WISATA DESA BANRAAS PULAU GILI IYANG MADURA MELALUI KELOMPOK SADAR WISATA - Enza Resdiana; Nur Inna Alfiyah; Laylatul Hasanah (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2021)
The Tourism Awareness Group is a self-help and self-help group that grows from, by and for the community and aims to increase regional tourism development and succeed in tourism development by becoming a government partner in increasing public awareness in the tourism sector, increasing human resources, encouraging the realization of Sapta Pesona, increasing product quality and tourism.This research uses descriptive qualitative method, which is the subject and object of this research is the Andang Taruna Village of Banraas Tourism Awareness Group (Pokdarwis). Iyang Madura).The role of Pokdarwis Andang Taruna is able to act as a driving force for the community where the community has provided support and a role as host in an effort to create a conducive environment and atmosphere that is able to encourage the growth and development of the tourism industry and the realization of charm. Whereas the role as a partner has been carried out by Pokdarwis Andang Taruna in the form of activities and programs involving the Government and other parties related to the development and construction of tourist facilities such as lodging, transportation, culinary delights and so on, although there has not been maximum cooperation between Pokdarwis and the Government so that there are obstacles in realizing the caring character of tourism.